Acute Myeloid Leukemia: analysis of epidemiological profile and survival rate - Mariana Cardoso de Lima; Denise Bousfield da Silva; Ana Paula Ferreira Freund; Juliana Shmitz Dacoregio; Tatiana El Jaick Bonifácio Costa; Imaruí Costa; Daniel Faraco; Maurício Laerte Silva (Elsevier, 2016)
Objective: To describe the epidemiological profile and the survival rate of patients with acute myeloid leukemia (AML) in a state reference pediatric hospital. Method: Clinical-epidemiological, observational, retrospective, descriptive study. The study included new cases of patients with AML, diagnosed between 2004 and 2012, younger than 15 years. Results: Of the 51 patients studied, 84% were white; 45% were females and 55%, males. Regarding age, 8% were younger than 1 year, 47% were aged between 1 and 10 years, and 45% were older than 10 years. The main signs/symptoms were fever (41.1%), asthenia/lack of appetite (35.2%), and hemorrhagic manifestations (27.4%). The most affected extra-medullary site was the central nervous system (14%). In 47% of patients, the white blood cell (WBC) count was below 10,000/mm3 at diagnosis. The minimal residual disease (MRD) was less than 0.1%, on the 15th day of treatment in 16% of the sample. Medullary relapse occurred in 14% of cases. When comparing the bone marrow MRD with the vital status, it was observed that 71.42% of the patients with type M3 AML were alive, as were 54.05% of those with non-M3 AML. The death rate was 43% and the main proximate cause was septic shock (63.6%). Conclusions: In this study, the majority of patients were male, white, and older than 1 year. Most patients with WBC count <10,000/mm3 at diagnosis lived. Overall survival was higher in patients with MRD <0.1%. The prognosis was better in patients with AML-M3. Resumo: Objetivo: Descrever o perfil epidemiológico e a taxa de sobrevida dos pacientes com Leucemia Mielóide Aguda (LMA), em um hospital pediátrico de referência estadual. Método: Estudo clínico-epidemiológico, observacional, retrospectivo e descritivo. Foram incluídos casos novos de pacientes com LMA, diagnosticados entre os anos de 2004 e 2012, com idade <15 anos. Resultados: Entre os 51 pacientes estudados, 84% eram da raça branca, 45% do sexo feminino e 55% do masculino. Quanto a faixa etária, 8% tinham idade <1 ano, 47% entre 1 e 10 anos e, 45% >10 anos. Os principais sinais/sintomas ao diagnóstico foram febre (41,1%), astenia/inapetência (35,2%) e manifestações hemorrágicas (27,4%). O Sistema Nervoso Central foi o local extra-medular mais acometido (14%). Em 47% dos pacientes a leucometria ao diagnóstico foi <10.000/mm3. A doença residual mínima (DRM) no 15° dia de tratamento foi <0,1% em 16% da casuística. Recidiva medular ocorreu em 14% dos casos. Ao se comparar a DRM da medula óssea com o status vital, observou-se que estavam vivos 71,42% dos pacientes com LMA tipo M3 e 54,05% daqueles com LMA não-M3. A taxa de óbito foi de 43% e a principal causa imediata foi o choque séptico (63,6%). Conclusões: Neste estudo, a maioria dos pacientes é do sexo masculino, raça branca, maiores que 1 ano de idade. A maioria dos pacientes com leucometria <10.000/mm3 ao diagnóstico está viva. A sobrevida global é maior nos pacientes com DRM <0,1%. O prognóstico é melhor nos pacientes com LMA-M3. Keywords: Acute myeloid leukemia, Leukemia, Children, Palavras-chave: Leucemia mielóide aguda, Leucemia, Criança